Application of the Coagulation Jar Test Method for the Treatment of Coal Wastewater in Industrial Wastewater Management - M.T., Ridwan,; Nahar, Nahar; Irwan, Irwan; Hasanah, Uswatun (Politeknik Negeri Lhokseumawe, 2025)
The coagulation test for coal wastewater was conducted using the jar test method to evaluate the performance of different coagulants under varying pH and dosage conditions. The coagulants used were FeCl₃, Al₂(SO₄)₃, and Poly Aluminium Chloride (PAC). The optimal conditions were determined by adjusting the pH (5, 6, 7, and 8) and varying the coagulant dosage at each pH level. The parameters analyzed included turbidity, pH, total suspended solids (TSS), and metal content. Laboratory results indicate that PAC is the most effective coagulant for reducing contaminants in coal wastewater. The optimal coagulation conditions were achieved at pH 8 with a PAC dosage of 1 ppm. The coagulants function by destabilizing colloidal particles, with their efficiency influenced by solubility and pH conditions. FeCl₃ and Al₂(SO₄)₃, as cationic coagulants, exhibit pH-dependent solubility, significantly lowering the pH of treated water compared to PAC. Conversely, PAC performs optimally in alkaline conditions and induces a smaller pH reduction. Overall, PAC demonstrated superior coagulation performance, achieving turbidity of 2.06 NTU, TSS of 5 mg/L, Fe content of 0.11 mg/L, Mn content of 0.01 mg/L, and Al content of 0.01 mg/L. These findings confirm that PAC is the most effective and efficient coagulant for treating coal wastewater.